MODEL DINAMIK PENANGANAN SAMPAH (STUDI KASUS SOSIAL MASYARAKAT DI DKI JAKARTA) - Sidik, M. Ansorudin (Jurnal Rekayasa Lingkungan)
Social dynamic of of waste management is rarely discussed in a paper. Using causal loop diagram, this issue will be analyzed in this paper based on the case study of waste management in Jakarta. Problems occurred in Jakarta were identified using metaplan method carried out by BPPT to explore social problem of solid waste management. It is started from the fact that for managing waste,the regional government tends to use the top down approach rather than bottom up approach. The analysis shows the result that the problems are dynamic as social problems always changes, not static. Such dynamic tendency can be anticipated in the future by the regional government in accordance with the social changes occurred to people live in Jakarta.Key Wods : social dynamic, waste management, model dinamic